Investigation of the relationship between skin-emitted volatile fatty acids and skin surface acidity in healthy participants—a pilot study. (7th April 2021) - Shetewi, Tasneem; Finnegan, Melissa; Fitzgerald, Shane; Xu, Shuai; Duffy, Emer; Morrin, Aoife
Abstract: Volatile organic compounds (VOCs) emitted from human skin are of great interest in general in research fields including disease diagnostics and comprise various compound classes including acids, alcohols, ketones and aldehydes. The objective of this research is to investigate the volatile fatty acid (VFA) emission as recovered from healthy participant skin VOC samples and to characterise its association with skin surface acidity. VOC sampling was performed via headspace-solid phase microextraction with analysis via gas chromatography-mass spectrometry. Several VFAs were recovered from participants, grouped based on gender and site (female forehead, female forearm, male forearm). Saturated VFAs (C9, C12, C14, C15, C16) and the unsaturated VFA C16:1 (recovered only from the female forehead) were considered for this study. VFA compositions and abundances are discussed in the context of body site and corresponding gland type and distribution, and their quantitative association with skin acidity investigated. Normalised chromatographic peak areas of the recovered VFAs were found to linearly correlate with hydrogen ion concentration measured at each of the different sites considered and is the first report to our knowledge to demonstrate such an association. Our observations are explained in terms of the free fatty acid content at the skin surface which is well-established as being a major contributor to skin surface acidity. Furthermore, it is interesting to consider that these VFA emissions from skin, governed by equilibrium vapour pressures exhibited at the skin surface, will be dependent on skin pH. It is proposed that these pH-modulated equilibrium vapour pressures of the acids could be resulting in an enhanced VFA emission sensitivity with respect to skin surface pH. To translate our observations made here for future wearable biodiagnostic applications, the measurement of skin surface pH based on the volatile emission was demonstrated using a pH indicator dye in the form of a planar colorimetric sensor, which was incorporated into a wearable platform and worn above the palm surface. As acidic skin surface pH is required for optimal skin barrier function and cutaneous antimicrobial defence, it is envisaged that these colorimetric volatile acid sensors could be deployed in robust wearable formats for monitoring health and disease applications in the future.